Health evaluation of employees occupationally exposed to methylene chloride: twenty-four hour electrocardiographic monitoring - Ott, M Gerald; Skory, Lyman K; Holder, BB; Bronson, Julie M; Williams, Paul R (Scandinavian Journal of Work, Environment & Health, 1983)
Reports concerning the potential of methylene chloride an? related chemicals to increase cardiac sensitivity to epinephrine and concerns stemming from the metabolism of methylene chloride to form carboxyhemoglobin prompted interest in the electrocardiographic monitoring of men with methylene chloride exposure. Fifty employees of two fiber production plants were selected for study, 24 of whom were occupationally exposed to methylene chloride. All the participants were white males between the ages of 37 and 63 years. Eleven of the men had reported a history of heart disease. Under the conditions of this study, neither an increase in ventricular or supraventricular ectopic activity nor episodic ST-segment depression was associated with exposure to methylene chloride that ranged from a time-weighted average of 60 ppm to a time-weighted-average of approximately 475 ppm.
Keywords: carboxyhemoglobin; electrocardiographic monitoring; employee; health evaluation; holter monitoring; methylene chloride; occupational exposure